Spectral and temporal resolutions of information-bearing acoustic changes for understanding vocoded sentencesa) - Stilp, Christian E. (J Acoust Soc Am, 2015)
Short-time spectral changes in the speech signal are important for understanding noise-vocoded sentences. These information-bearing acoustic changes, measured using cochlea-scaled entropy in cochlear implant simulations [CSE(CI); Stilp et al. (2013). J. Acoust. Soc. Am. 133(2), EL136–EL141; Stilp (2014). J. Acoust. Soc. Am. 135(3), 1518–1529], may offer better understanding of speech perception by cochlear implant (CI) users. However, perceptual importance of CSE(CI) for normal-hearing listeners was tested at only one spectral resolution and one temporal resolution, limiting generalizability of results to CI users. Here, experiments investigated the importance of these informational changes for understanding noise-vocoded sentences at different spectral resolutions (4–24 spectral channels; Experiment 1), temporal resolutions (4–64 Hz cutoff for low-pass filters that extracted amplitude envelopes; Experiment 2), or when both parameters varied (6–12 channels, 8–32 Hz; Experiment 3). Sentence intelligibility was reduced more by replacing high-CSE(CI) intervals with noise than replacing low-CSE(CI) intervals, but only when sentences had sufficient spectral and/or temporal resolution. High-CSE(CI) intervals were more important for speech understanding as spectral resolution worsened and temporal resolution improved. Trade-offs between CSE(CI) and intermediate spectral and temporal resolutions were minimal. These results suggest that signal processing strategies that emphasize information-bearing acoustic changes in speech may improve speech perception for CI users.